Building trust in an integrated care system: a leader's experience. Issue 6 (2nd June 2021) - Webster, Rob
Abstract : Achieving success as an integrated care system can be fraught with challenges. Rob Webster CBE, CEO Lead for the West Yorkshire and Harrogate Health and Care Partnership, explains why trust is integral to overcoming these challenges and making a real difference to local communities.